2016
DOI: 10.1590/0037-8682-0454-2015
|View full text |Cite|
|
Sign up to set email alerts
|

High prevalence of plasmid-mediated quinolone resistance determinants in Enterobacter cloacae isolated from hospitals of the Qazvin, Alborz, and Tehran provinces, Iran

Abstract: Introduction: Plasmid-mediated quinolone resistance (PMQR) is a growing clinical concern worldwide. The main aims of this study were to detect qnr-encoding genes and to evaluate the clonal relatedness of qnr-positive Enterobacter cloacae isolates. Methods: A total of 116 E. cloacae isolates that were not susceptible to quinolone were obtained from seven hospitals in Tehran, five hospitals in Qazvin, and two hospitals in Karaj (Iran). Bacterial identification was performed using standard laboratory methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
(35 reference statements)
3
8
0
Order By: Relevance
“…In concordance with other reports, qnrA1 and qnrS1 genes were rarely found in our study 6,22,28. Similar to qnrB , all isolates with qnrA1 determinants belonged to the main clone A.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In concordance with other reports, qnrA1 and qnrS1 genes were rarely found in our study 6,22,28. Similar to qnrB , all isolates with qnrA1 determinants belonged to the main clone A.…”
Section: Discussionsupporting
confidence: 93%
“…isolates. They prevailed in isolates from Iran,28 Tunisia,22 Italy,29 and Algeria30 In our study, qnrB4 was found in one isolate only. This is in contrast with reports from some European countries, where qnrB4 is the main detected allele 31,32…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Attaining complete cure from UTIs caused by E. coli is highly challenging, and the presence of qnr genes and ESBLs production are said to be most responsible. However, some other factors such as the overexpression of efflux pump or declined intracellular concentration and mutations (in topoisomerase IV and DNA gyrase enzymes) could also be equally effective in this regard [12, 30, 31]. On the other hand, quinolones are the most prescribed antibiotics for UTI therapy in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…(25.71%) and Mahmoud et al 32 (20%). However, lower results (12.6%) were obtained by Biendo et alin India 35 .…”
mentioning
confidence: 90%